Sustainable approaches for nickel removal from wastewater using bacterial biomass and nanocomposite adsorbents: A review. (March 2022) - Noman, Efaq; Al-Gheethi, Adel; Saphira Radin Mohamed, Radin Maya; Al-Sahari, Mohamed; Hossain, Md Sohrab; Vo, Dai-Viet N.; Naushad, M.
Abstract: In this article, the nickel (Ni 2+ ) ions removal from the wastewater is reviewed. Adsorption is widely used to remove Ni 2+ ions from waters and wastewaters. The usage of biomass is becoming more common for Ni 2+ ions removal, while the commercial activated carbon from different agriculture wastes is preferred as an adsorbent for Ni 2+ ion removal. The present review aimed to organise the available information regarding sustainable approaches for Ni 2+ ions removal from water and wastewaters. These include adsorption by nanoparticles, bacterial biomass, and activated carbon from agriculture wastes, since they are the most common used for the Ni 2+ ions removal. The bacterial and agricultural waste adsorbents exhibited high efficiency with a renewable source of biomass for Ni 2+ ion removal. The biosorption capacity of the Ni 2+ ions by the bacterial biomass range from 5.7 to 556 mg/g, while ranging from 5.8 to 150 mg/g by the activated carbon from different organic materials. The biosorption capacity of the nanocomposite adsorbents might reach to 400 mg/g. It appeared that the elimination of nickel ions need a selective biomass adsorbent such as the tolerant bacterial cells biomass which acts as a store for Ni 2+ ion accumulations as a results for the active and passive transportation of the Ni 2+ ions through the bacterial cell membrane. Graphical abstract: Image 1 Highlights: The removal of nickel ions by sustainable approaches was reviewed. Adsorption takes place by electrostatic, attraction and interaction. The nickel elimination needs a selective biomass adsorbent specific adsorption conditions.